(untitled) (Global Journal of Sciences, 2025)
The decisions and emotions of people are highly influenced by food pattern which plays a vital role in their daily activities. Dieting patterns differ in terms of the goals set by a certain individual. People are advised to know how to regulate their diets and select eating habits that will promote health by preventing food-related diseases. Six diet styles were evaluated and ranked by considering multiple important factors utilizing a multi-criteria decision-making algorithm; the fuzzy Preference Ranking Organization Method for Enrichment Evaluations (fuzzy PROMETHEE). Of all considered diet styles, the low-carb diet ranked first diet style with a net flow of 0.2066, and the intermittent diet ranked sixth with a net flow of -0.3232; however, depending on the chosen criteria and assigned weights, the outcomes would change dramatically when weights are modified according to the specific person’s profile. This study will help individuals, dieticians, and nutritionists make appropriate diet plans by choosing which pattern to follow with awareness of the probable risk and consequences associated with their choice.